Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae) - Melo, Bruno F. [UNESP] (Magnolia Press, 2017)
Cyphocharax boiadeiro, new species, is described from the upper rio Araguaia, a tributary of the Amazon basin in central Brazil. The new species is readily distinguished from its congeners by the presence of a distinct longitudinal dark stripe from supracleithrum to the caudal peduncle and by a combination of morphometric, meristic, and pigmentation features. Morphological characters supporting putative subunits of Cyphocharax are also discussed.
Keywords: Biodiversity; morphology; Neotropical fishes; South America; taxonomy